2010
DOI: 10.1038/ajh.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Korean Red Ginseng (Panax ginseng C.A. Mayer) and Its Isolated Ginsenosides and Polysaccharides on Arterial Stiffness in Healthy Individuals

Abstract: Although preliminary, this study is the first to demonstrate that KRG may improve arterial stiffness as measured by AI. In addition, it appears that ginsenosides may be the principal pharmacologically active component of the root, rather than the polysaccharide fraction. This study supports the results seen with KRG in the preclinical studies and warrants further investigation on acute and long-term endothelial parameters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 18 publications
1
41
0
Order By: Relevance
“…A limited number of investigations of vasoactivity in humans have mainly pursued the antihypertensive potential of ginseng, yielding largely equivocal results, where blood pressure (BP) was reduced, remained unchanged, or was increased [8][9][10][11]. Despite contentious BP effects, more discriminate hemodynamic analyses of the arterial pressure waveform, comprising the first phase of our present study, demonstrated marked decreases in pressure wave reflection following acute KRG intake [12], suggestive of lower peripheral resistance and improved distensibility.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…A limited number of investigations of vasoactivity in humans have mainly pursued the antihypertensive potential of ginseng, yielding largely equivocal results, where blood pressure (BP) was reduced, remained unchanged, or was increased [8][9][10][11]. Despite contentious BP effects, more discriminate hemodynamic analyses of the arterial pressure waveform, comprising the first phase of our present study, demonstrated marked decreases in pressure wave reflection following acute KRG intake [12], suggestive of lower peripheral resistance and improved distensibility.…”
Section: Introductionmentioning
confidence: 89%
“…Our protocol featured a 3 g dose of ginseng root and bioequivalent doses of the two extracts. Three gram dose was chosen because it was previously found to be efficacious [12] and it is situated within the 0.5-9 g dose range currently recommended in established monographs including German Commission E and Canadian NHPD monograph [36,37]. Administration of doses that are bioequivalent to the root and of the same batch allowed for an unconfounded comparison between the root and its isolated fractions.…”
Section: Discussionmentioning
confidence: 99%
“…In a separate study [15], one-time treatment with KRG (50 mg/kg) decreased the mean BP and heart rate in 12 healthy, non-smoking male volunteers [15]. In contrast, other studies have shown no effect of ginseng on BP [16][17][18], as neither long-term (12 weeks) [16] nor one-time treatment [17] with North American ginseng significantly changed the BP in patients with hypertension. These discrepant reports may be attributable to the heterogeneity of ginsenoside preparations or differences among the study subjects.…”
Section: Discussionmentioning
confidence: 83%
“…Therefore, our data suggest that KRG may reduce the risk for major cardiovascular events by reducing vascular stiffness in the central aorta and peripheral muscular arteries in patients with stable CAD. In a separate study, onetime treatment with KRG or a ginsenoside extract, but not a polysaccharide extract, decreased the augmentation index, but not BP, in healthy subjects [18]. The augmentation index is a commonly used measure of arterial stiffness and an independent marker of increased total and cardiovascular mortality [22].…”
Section: Discussionmentioning
confidence: 99%
“…29) Previously, we found that oral administration of total extract of RG prior to vaccination enhanced anti-influenza virus antibody responses, and that the mice receiving total extract of RG gave better antibody responses than those receiving RG saponin. 30) In the same situation we have found that oral administration of RG polysaccharide has little or no effect on antibody responses (data not shown).…”
Section: Discussionmentioning
confidence: 99%